Analysis Of Stock Returns On The Asean Stock Exchange In 2024 In Support Of SDGS 3 Moderated By Company Size - Fitria, Nurul; Yuhertiana, Indrawati; Sundari, Siti (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of Sales Growth, Debt to Equity Ratio (DER), and Environmental, Social, and Governance (ESG) Disclosure on stock returns, as well as to examine the role of company size as a moderating variable in health sub-sector companies listed on the ASEAN Stock Exchange in 2024. The health sector was chosen based on its contribution to the achievement of Sustainable Development Goal (SDG) 3, namely Good Health and Well-Being. This study uses secondary data in the form of financial reports and sustainability reports that contain GRI 2, 300, and 400 standards. Of the total population of 147 companies, 75 companies met the purposive sampling criteria. Data analysis was conducted using Moderated Regression Analysis (MRA). The results showed that all variables affected stock returns. The moderation results indicated that company size did not moderate sales growth and DER on stock returns. However, company size was found to strengthen the effect of ESG Disclosure on stock returns. This study makes an important contribution by showing that sustainability disclosure not only creates a positive image for companies but can also increase stock returns. The increase in stock returns supports the achievement of SDG 3 through increased investor interest, which encourages more investment funds for sustainable health business practices.